التغير التنظيمي لجامعة التكوين المتواصل وعلاقته بجودة التعليم العالي: دراسة ميدانية بجامعة التكوين المتواصل بالوادي - قريشي, الزهرة (University of Eloued جامعة الوادي, 2021)
تهدف هذه الدراسة إلى التعرف على علاقة التغيير التنظيمي بجودة التعليم العالي بجامعة التكوين المتواصل بالوادي، و قد إنطلقت الدراسة من فرضية عامة مؤداها أنه توجد علاقة ارتباطية ذات دلالة إحصائية بين التغيير التنظيم يوجودة التعليم العالي بجامعة التكوين المتواصل بالوداي، وتفرعت عنها مجموعة من الفرضيات الفرعية تتعلق بأبعاد جودة التعليم العالي . إعتمدنا على المنهج الوصفي التحليلي لأنه يناسب الدراسة ،وتم إستخدام أداتي الإستبيان و المقابلة الميدانية لجمع البيانات من أفراد العينة ، والتي تكونت من مجموعتين ، الأولى بلغ تعدادها 30 فردا من الأساتذة، و الثانية بلغ تعدادها 110 فردا من طلبة جامعة التكوين المتواصل بالوادي للموسم الجامعي 2019/2020 ،و تم الإعتماد على برنامج SPSS لمعالجة البيانات ،و إستخدام الأساليب الإحصائية المناسبة لإختبار الفرضيات . توصلت الدراسة إلى إثبات صحة الفرضية العامة، و هي وجود علاقة ارتباطية بين التغيير التنظيمي بكل أبعاده وبين جودة التعليم العالي بكل أبعادها، بالإضافة إلى إثبات صحة الفرضيات الجزئية و إنتهت الدراسة بمجموعة من التوصيات و الإقتراحات لفائدة جامعة التكوين المتواصل وكل مؤسسات التعليم العالي . This study aims to identify the relationship of organizational change with the quality of higher education at the University of Continuous Training in Eloued Thestudy started from a general hypothesis that there is a correlation with statistical significance between organizational change and the quality of higher education at the University of Continuous Training in Eloued, and a group of sub hypotheses related to dimensions Quality of higher education. We relied on the analytical descriptive approach because it is suitable for the study, in addition to questionnaire and field interview tools to collect data from the sample members, which consisted of two groups, the first numbering 30 professors, and the second with a population of 110 individuals from the University of Continuing Formation in Eloued for the academic year 2019/2020 , we relied on the SPSS program for data processing, and appropriate statistical methods were used to test hypotheses. The study proved the validity of the general hypothesis, which is the existence of a correlation between organizational change in all its dimensions and the quality of higher education in all its dimensions, in addition to proving the validity of partial hypotheses, and the study ended with a set of recommendations and suggestions for the benefit of the Continuous Training University and all higher education institutions.
أطروحة دكتوراه في علم الاجتماع تخصص المنظمات و الموارد البشرية و الاتصال
Keywords: التغيير التنظيمي، الجودة الشاملة، جودة التعليم العالي، جامعة التكوين المتواصل.; Organizational Change , Total Quality , Quality of Higher Education , University of Continuing Education .